Memory reconsolidation in psychotherapy for severe perfectionism within borderline personality. Issue 11 (21st September 2020) - Vaz, Alexandre; Ecker, Bruce
Abstract: Objective(s): For a case of severe perfectionism, comorbid with complex trauma symptomatology including suicidality, self‐harming, and other markers of borderline personality, we demonstrate the use of the empirically confirmed process identified in memory reconsolidation (MR) research for the unlearning and nullification, or "erasure, " of emotional and behavioral responses driven by learned expectations and mental models. MR has been proposed as a transtheoretical, unifying mechanism underlying profound psychotherapeutic change. The therapist (first author), under the second author's supervision, used a varied set of clinical skills woven together through a focus on the MR process. Results: The result was a depotentiation of underlying, traumatic emotional learnings and near‐total disappearance of perfectionistic and self‐harming behaviors, urges and attitudes after 1 year of therapy. Conclusions: Implications of this case are discussed in terms of symptom generation by implicit emotional learnings and MR as a promising framework for advancing the effectiveness and unification of psychotherapy.